The differential effect of background music on memory for verbal and visuospatial information. Issue 4 (2nd October 2019) - Echaide, Claudia; del Río, David; Pacios, Javier
Abstract: Background music is a part of our everyday activities. Considerable evidence suggests that listening to music while performing cognitive tasks may negatively influence performance. However, other studies have shown that it can benefit memory when the music played during the encoding of information is also provided during the retrieval of that information, in the so-called context dependent memory effect . Since controversial results may be attributed to the nature of the material to be memorized, the aim of the present study is to compare the potential effect of consistent background music on the immediate and long-term recall of verbal and visuospatial information. Experiment 1 showed that instrumental background music does not benefit nor decrease recall of a list of unrelated words, both at the immediate and the 48-hours-delayed tests. By contrast, Experiment 2 revealed that the same background music can impair immediate and therefore long-term memory for visuospatial information. Results are interpreted in terms of competition for neurocognitive resources, with tasks mostly relying on the same brain hemisphere competing for a limited set of resources. Hence, background music might impair visuospatial memory to a greater extent than verbal memory, in the context of limited capacity cognitive system. In conclusion, the nature of the material to be learnt must be considered to fully understand the effect of background music on memory.